Handbook of computational economics - Amman, Hans M.; Kendrick, David A.; Rust, John, 1955- (Amsterdam ; New York : Elsevier, 1996)
This handbook volume surveys recent research on Agent-based Computational Economics (ACE), the computational study of economic processes modeled as dynamic systems of interacting agents. Empirical referents for "agents" in ACE models can range from individuals or social groups with learning capabilities to physical world features with no cognitive function. Topics covered include: learning; empirical validation; network economics; social dynamics; financial markets; innovation and technological change; organizations; market design; automated markets and trading agents; political economy; social-ecological systems; computational laboratory development; and general methodological issues. Every volume contains contributions from leading researchers. Each Handbook presents an accurate, self-contained survey of a particular topic. The series provides comprehensive and accessible surveys
v. 1. [without special title] -- v. 2 Agent-based computational economics / edited by Leigh Tesfatsion and Kenneth L. Judd.
Includes bibliographical references and index.
rpm 01/11/13
Loans
Keywords: Economics, Mathematical; Econometrics; Equilibrium (Economics); Computer simulation